Persepsi Perawat sebagai Edukator Berhubungan dengan Implementasi Discharge Planning - Pakpahan, Martina; Rangga, Fransiska Denata; Vasquien, Sandra; Octaria, Martha (Jurnal Kesehatan Holistic, 2020)
The nurses as an educator becomes an important part in the implementation of discharge planning. The implementation of the optimal Discharge planning can increase the length of stay in hospital, readmission, and financing. The aim of the study to identify the correlation between nurse's perception as an educator with the implementation of Discharge Planning by nurses. This research was a quantitative study with cross sectional design. Sampling technique used the total sampling with 43 nurses in the inpatient room in one central Indonesian private hospital as a respondents. Data collection was carried out using questionnaires and observation. Data analysis in the form of univariate and Bivariat. Bivariate analysis using Chi Square test. The univariate analysis was found by 40 (93.02%) Respondents had negative perception and to 36 (83.72%) The respondent did not implement discharge planning according to standard operating procedures. Bivariat analysis found the correlation between the perception of nurses as an educator with the implementation of discharge planning by nurses (p value 0.001). The hospitals can develop a positive perception of nurses as an educator through training and mentoring in carrying out standard discharge planning. Further research can examine the correlation of other variables on the implementation of discharge planning.